Analysis of rice profitability and marketing in Jakarta. Issue 1 (February 2021) - Nurmalinda; Waryat; Aminah, S; Irawati, A F C; Yanis, M; Maharani, W S; Ammatillah, C S
Abstract: Jakarta as a metropolitan area has rice fields spread across three urban areas. The rice marketing was usually conducted directly over harvest time, either to collectors who come to the harvest location or sell them to Subang or Indramayu. The aim of the study was to examine rice profitability and marketing in Jakarta. The study was carried out in three regions of Jakarta, namely North, West and East of Jakarta, through survey method. The respondents were 46 farmers with direct interview techniques. The profitability of rice farming was analyzed by using cost and revenue analysis, while rice marketing was analyzed by using qualitative descriptive. The results showed that rice farming in Jakarta was still profitable with the R/C ratio greater than one. The marketing chain of rice in Jakarta was generally very short. The farmers mostly sold the rice directly to large traders (Jakarta-Outside Trader; 85%), only a small proportion (15%) sold to regional collectors. As much as 90% of the grain was sold to the traders and 10% was used as seed or consumption. The selling price of rice was determined by traders based on quality of grain. The non-hulled rice price ranged Rp 4200-4500 per kg.